Reminiscence of Classical Chaos in Driven Transmons - Joachim Cohen; Alexandru Petrescu; Ross Shillito; Alexandre Blais (PRX Quantum, 2023)
Transmon qubits are ubiquitously used in superconducting quantum information processor architectures. Strong drives are required to realize fast, high-fidelity, gates and measurements, including parametrically activated processes. Here, we show that even off-resonant drives, in regimes routinely used in experiments, can cause strong modifications to the structure of the transmon spectrum rendering a large part of it chaotic. Accounting for the full nonlinear dynamics of the transmon in a Floquet-Markov formalism, we find that these chaotic states, often neglected through the hypothesis that the anharmonicity is weak, strongly impact the lifetime of the transmon’s computational states. In particular, we observe that chaos-assisted quantum phase slips greatly enhance band dispersions. In the presence of a measurement resonator, we find that approaching chaotic behavior correlates with strong transmon-resonator hybridization, and an average resonator response centered on the bare resonator frequency. These results lead to a photon-number threshold characterizing the appearance of chaos-induced quantum demolition effects during strong-drive operations, such as dispersive qubit readout. The phenomena described here are expected to be present in all circuits based on low-impedance Josephson junctions.